Powerful words, false solutions: decolonising modern slavery discourse in Malaysia - Beh, Lih Yi (2022)
‘Modern slavery’ has been popularised as a discourse to describe different forms of exploitation of human beings. The concept has been conceived in the West, adopted by groups like the United Nations and international advocacy groups. Modern slavery is said to be most prevalent in Africa and Asia, where many of the countries are former European colonies. Yet ‘modern slavery’ has also come under increasing scrutiny for its limitations and vagueness. This paper adds to the field of study by critically examining how widely accepted the notion of modern slavery in Malaysia is and whether it is an effective discourse in resolving labour exploitation issues. Based on a case study and interviews with leading Malaysian migrant rights’ campaigners, this research shows that the use of the term modern slavery in the Malaysian public discourse is limited because of its inadequacy to encapsulate the underlying problems of labour exploitation. The global economic inequality that is a product of colonial legacies has continued to push people from the Global South to risk their lives for better economic opportunities. Utilising Fanon’s theory of colonial Manichaeism (1963) and Mignolo’s concept of delinking (2011), this paper asserts that if the world wants to put an end to modern slavery, then it ought to address the legacy of colonialism and the system that is underpinning the modern capitalist economy to eradicate these problems. It proposes a departure from the modern slavery discourse and to reframe the issue by focusing on economy inequality and the capitalist system that perpetuates labour exploitation.